Case of needle tract seeding during preoperative neoadjuvant chemotherapy for resectable pancreatic cancer. Issue 1 (9th May 2022) - Yane, Kei; Aoki, Mai; Tomita, Yusuke; Yoshida, Masahiro; Morita, Kotaro; Ihara, Hideyuki; Sumiyoshi, Tetsuya; Kondo, Hitoshi; Oyamada, Yumiko
Abstract: Reports of needle tract seeding (NTS) as a complication of endoscopic ultrasound‐guided fine‐needle aspiration (EUS‐FNA) have been increasing. To date, most of the reported cases of NTS have been diagnosed during the postoperative follow‐up period. Herein, we report a case of NTS that occurred during preoperative neoadjuvant chemotherapy after EUS‐FNA for resectable pancreatic cancer. The patient underwent transgastric EUS‐FNA for a pancreatic tail tumor. He was diagnosed as having resectable pancreatic cancer and received preoperative neoadjuvant chemotherapy. After completion of the chemotherapy, computed tomography showed a thick‐walled cyst‐like structure appearing between the pancreas and the gastric wall. Combined resection revealed adenocarcinoma invasion into the cyst‐like structure. Based on the clinical course, and surgical and pathological findings, the condition was diagnosed as NTS. It is thus crucial that after EUS‐FNA, a detailed review of the imaging findings be conducted in the preoperative period. If adhesions between the stomach and the pancreas are observed after transgastric EUS‐FNA, combined resection of the gastric wall should be considered.